Oviposition Deterrence and Larvicidal Activity of Propyl Ether Dillapiole and Piperidyl Dillapiole Against Aedes (Stegomyia) aegypti (Diptera: Culicidae) - Junielson Soares da Silva; Ana Cristina da Silva Pinto; Samara Silva de Souza; Francisco Célio Maia Chaves; Sabrina da Fonseca Meireles; Rosalina Pinheiro Pereira; Rosemary Aparecida Roque; João Marcelo de Castro e Sousa; Míriam Silva Rafael (Toxics)
The study of substances of botanical origin is fundamental for the development of new effective alternatives for the control of Aedes (Stegomyia) aegypti (Culicidae), a vector of arboviruses in humans. In this study, the potential of two new dillapiole derivatives, propyl ether dillapiole and piperidyl dillapiole, was tested to determine their ability to deter oviposition and their larvicidal and residual effects against Ae. aegypti under simulated field conditions, as alternatives for the control of this mosquito. The ability of these substances to deter oviposition by pregnant Ae. aegypti females was assessed in the laboratory, and then the larvicide and residual effects of different concentrations were tested under simulated field conditions. The determination of the enzymatic activity in exposed larvae was carried out using sublethal concentrations. The LC50 values of propyl ether dillapiole after 24 and 48 h were 24.60 µg/mL and 14.76 µg/mL, and those of piperidyl dillapiole were 31.58 µg/mL and 24.85 µg/mL, respectively. After 48 h of exposure to aged, treated water, the mortality of propyl ether dillapiole (100 µg/mL) and piperidyl dillapiole (200 µg/mL) fell to 81.7% and 75% on the second day, and to 73.3% and 66.7% on the fourth day, respectively. The concentrations of 100 µg/mL of propyl ether dillapiole and 200 µg/mL of piperidyl dillapiole caused oviposition rates of only 3.80% and 4.63% of the eggs of the females, respectively, compared to 22.01% in the negative control (water and DMSO at 2%). In the larvae exposed to propyl ether, piperidyl dillapiole, dillapiole, or the chemical insecticide temephos (positive control), inhibition of acetylcholinesterase (AChE) occurred. Propyl ether dillapiole and piperidyl dillapiole have potential for use as alternative forms of control of Ae. aegypti, with propyl ether dillapiole being the most promising molecule. Further studies are needed to understand the effects of these substances on this mosquito and on non-target organisms.